2016
DOI: 10.1016/j.jaci.2016.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Platelets constitutively express IL-33 protein and modulate eosinophilic airway inflammation

Abstract: Our novel findings suggest that platelets might be important cellular sources of IL-33 protein in vivo and that platelet-derived IL-33 might play a role in airway inflammation. Therefore platelets might become an attractive novel therapeutic target for asthma and probably allergic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 56 publications
2
41
0
2
Order By: Relevance
“…1) [39]. In food allergy and anaphylaxis research, novel techniques were developed allowing the in-vivo monitoring of effects by allergen challenges, and, in accordance with the 3R principle, networks are formed to share tissues [70]. Future research directions may address the development of novel engineered mouse models facilitating the investigation of single-target molecules, whereas domestic animals represent natural animal models, spontaneously developing asthma, food allergy and anaphylaxis with immune mechanisms more similar to human allergy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) [39]. In food allergy and anaphylaxis research, novel techniques were developed allowing the in-vivo monitoring of effects by allergen challenges, and, in accordance with the 3R principle, networks are formed to share tissues [70]. Future research directions may address the development of novel engineered mouse models facilitating the investigation of single-target molecules, whereas domestic animals represent natural animal models, spontaneously developing asthma, food allergy and anaphylaxis with immune mechanisms more similar to human allergy.…”
Section: Resultsmentioning
confidence: 99%
“…The study highlighted the importance of IL-33 and mast cells to trigger anaphylaxis and might lead to novel anti-IL-33 therapeutics in humans [69]. Interestingly platelets, which participate in the anaphylactic reaction, have proven a significant source of IL-33 in humans as well as in an airway eosinophilia model in mice [70]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, IL-33 has been shown to mediate eosinophilo-poesis in response to Alternaria and enhance IL-5 expression by ILC2’s in the lungs. (24) This study along with a report by Takeda(25) which demonstrated that human platelets are a source of IL-33 implicate the importance of this cytokine in airway inflammation which may occur in response to environmental allergen exposure. Additionally, the interaction of genetics and fungal exposures has been investigated.…”
Section: Responses To Environmental Fungimentioning
confidence: 58%
“…33 In addition, platelet-derived IL-33 was recently suggested to induce eosinophilic airway inflammation. 34 On the other hand, PF4 was found to be a negative regulator of Th17 differentiation, thereby limiting cardiac allograft rejection in a murine cardiac transplant model. 35 Platelets also release microparticles, which are small extracellular vesicles (the majority are ;200 nm in diameter) produced via blebbing and fission of the plasma membrane.…”
mentioning
confidence: 99%